Crustal deformation in the Cathaysia Block, South China: insights from receiver function analysis - Tan, Ping; Duan, Yonghong; Wei, Yunhao; Tan, Yujuan; Zhao, Yanna (Frontiers in Earth Science, 2025)
The Cathaysia Block, a pivotal tectonic unit in South China, possesses a complex crustal architecture shaped by multi-phase tectonic evolution. This study integrates harmonic analysis of crustal anisotropy with an advanced H-κ-c stacking method applied to teleseismic receiver functions from 185 stations, to investigate crustal thickness (H), Vp/Vs ratio (κ), and anisotropic characteristics. The results reveal significant spatial heterogeneity: crustal thickness ranges from 24.5 to 36.6 km, while Vp/Vs ratios (1.65–1.84) indicate a compositional transition from felsic-dominated inland regions to mafic-enriched coastal zones. Crustal anisotropy, quantified by fast polarization directions (FPDs) and delay times (0.06–0.46 s), exhibits systematic spatial variations. In eastern Cathaysia, FPDs systematically rotate from NW-SE in the north to NNW-SSE in the south, aligning with the subduction trajectory of the Paleo-Pacific Plate. This pattern, along with crustal thinning, reflects extension induced by slab rollback, associated with mantle upwelling and underplating. Conversely, in western Cathaysia, E-W trending FPDs primarily reflect NW-SE compressive stresses imparted by Paleo-Pacific Plate subduction. Post-rollback thermal relaxation and widespread granitic emplacement subsequently enhanced crustal strength, promoting brittle fracture over ductile flow during regional extension. Collectively, this study elucidates the interplay between Paleo-Pacific Plate dynamics, crustal deformation mechanisms (brittle vs. ductile), and compositional evolution in shaping the tectonic architecture of the Cathaysia Block.